Factors Involved in Success of Poultry Business in Selected Areas of Tamilnadu - Vetrivel, S. C; Somasundaram, R (Journal of Commerce and Trade, 2013)
The poultry industry provides a good employment opportunity for both males and females along with agricultural activities. The poultry industries were involved with live stock, which is monitored around the clock and the poultry entrepreneurs are very much concentrated in utilizing the farm optimally enriching maximum output through selling the eggs and other allied products like feathers, gunny bags and poultry litters etc. The poultry entrepreneurs have gained a good profit and a particular portion of the profit was correctly paid towards income tax. Hence, the Indian economy gain the momentum through poultry industries. But after the introduction of globalization, many foreign countries launched their business in various areas namely production, marketing, transporting, banking, insurance, IT and IT enabled industries. The state government has not planned well to distribute the electricity power equally for already existing industries, the newly arrived foreign originated industries and service oriented organization. This affected drastically and the frequent power cuts were vested with the shoulders of poultry farms and feed mills and poultry egg packaging industries. Due to this frequent power cut, the agriculturalist in the dry land finds difficult to produce first quality maize, which is the core raw material for poultry feed. Hence, after liberalization many of the small poultry entrepreneurs were found very difficult to produce the quality eggs in their poultry farms and these eggs finds difficult to compete in the global market.